Spatial Distribution and Problems in the Interpretation of Radiocarbon Dates of the Sungir Site, Russia - Soldatova, Taisiya (Radiocarbon, 2019)
The Upper Paleolithic open-air site Sungir is located in the central Russian Plain. The blank production of the lithic industry is characterized by parallel reduction with flakes being the main blank type. The tool assemblage has two components: archaic types (Mousterian-like) on the one hand and Upper Paleolithic types on the other. The available data does not allow for a confident determination of the chronological position of the Sungir site, nor does it enable researchers to distinguish different stages of human occupation. The horizontal distribution of the dated samples demonstrates the almost complete absence of radiocarbon (14C) dates for household features identified at the site (fireplaces, fire and ritual pits, large accumulations of bones, etc.). In addition, the vertical distribution of 14C dates in the rather thick cultural layer points to the exposure of the site to solifluction.
CRIS-Team Scopus Importer:2019-08-06
Keywords: Aurignacian; Early Upper Paleolithic; radiocarbon chronology; spatial distribution; Streletskian culture; Sungir site